Mechanisms of Bushenyiqi decoction in the treatment of asthma: an investigation based on network pharmacology with experimental validation - Qin, Ziwen; Chen, Yujuan; Liu, Na; Wang, Yonggang; Su, Lili; Liang, Bin; Huang, Chuanjun (Frontiers in Pharmacology, 2024)
This study was supported by the Natural Science Foundation of Shandong Province Youth Program of China (NO. ZR2023QH089). All people who contributed Conclusions: In conclusion, the integration of network pharmacology and biological experiments has demonstrated that key constituents of BYD, such as quercetin, kaempferol, and luteolin, exhibit targeted effects on IL-6, EGFR, and HIF1A in combating asthma-related inflammation through inhibition of the PI3K/AKT signaling pathway.The findings of this investigation provide evidence supporting the effectiveness of TCM's "bushenyiqi" therapy in asthma management, as corroborated by contemporary medical technology.